Association between students' inattentiveness to study and their psychological conditions during the COVID-19 pandemic / Md. Muniruzzaman and Md. Roknuzzaman Siddiky - Muniruzzaman, Md; Siddiky, Md. Roknuzzaman (Universiti Teknologi MARA, 2021)
While the COVID-19 pandemic has adverse effects on the state of mental health of the individuals, no attention has been paid so far in the academia whether there is an association between students' inattentiveness to study and their psychological conditions during the COVID-19 pandemic. As such, the study was intended to find out the association between students' inattentiveness to study and their psychological conditions during this pandemic. Primary data for this study were collected from a total of 157 samples chosen from the undergraduate students of 18 academic departments of the Noakhali Science and Technology University (NSTU), Bangladesh on the basis of snowball sampling. The study reveals that most of the respondents were much inattentive to study during the COVID-19 pandemic and they were much anxious, depressed, tensed, restless, bored and frightened, and thereby their mental health and well-being were affected. The study shows that there is a strong positive association between the students' inattentiveness to study and their psychological conditions which involve anxiety, depression, tension, restlessness, boredom and fear/panic. The study indicates that the association between the students' inattentiveness to study and their psychological conditions is statistically significant. Finally, the study suggests that the Government and the authority concerned should undertake proper measures to mitigate the adverse psychological conditions of the NSTU students by means of motivations and psychosocial counselling, and thereby keeping up their attentiveness to study during the pandemic or any other critical situation. As such, there is a crying need for establishing a psychosocial counselling centre or an educational counselling centre in all universities of Bangladesh including the NSTU.